EFEKTIVITAS PENGELOLAAN KREDIT GUNA MENINGKATKAN PROFITABILITAS PADA PD. BPR BKK KEBUMEN KANTOR CABANG GOMBONG - Dwi Suprajitno (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
ABSTRACT BPR BKK Kebumen Branch Office Gombong is the bank crediting of the people. Therefore crediting an important factor that needs serious attention rather not exposed to bad loans. Effective credit management can be determined by calculating the Non Performing Loan (NPL). Non Performing Loan (NPL) below 5% to be an indicator of the effectiveness of the credit. The effectiveness of the credit management will contribute to the profitability of banks. Therefore it is necessary to work assessment to determine the development bank credit management and the level of profitability of each period. The objective of this study was to determine the effectiveness of the management of credit and to determine the level of profitability of the bank during the months from January to December 2015 at the PD. BPR BKK Kebumen Branch Office Gombong. The analysis used in this study is the ratio of bank crediting the use of Non Performing Loan (NPL), and bank profitability ratios is Gross Profit Margin (GPM), Net Profit Margin (NPM), BOPO and Return on Assets (ROA). The results showed credit management in PD. BPR BKK Kebumen Branch Office Gombong can already be said to be effective because it has met the standards with NPL levels below 5%. Effective management of credit at the bank helps in improving the profitability of the banks of the month from January to December 2015 although still fluctuating. Keywords: Effectiveness, Credit, Profitability